Mechanism of IGF2BP2 regulation of PPAR-γ/GLUT4 pathway in insulin resistance induced by sodium arsenite exposure in HepG2 cells - Shiqing XU; Zhida HU; Qiyao ZHANG; Siqi ZHAO; Yujie WANG; Xiaohui WANG; Teng MA; Li WANG (环境与职业医学)
BackgroundArsenic is an environmentally harmful substance that causes hepatic insulin resistance and liver damage, increasing the risk of type 2 diabetes mellitus. ObjectiveTo explore whether the insulin-like growth factor 2 mRNA binding protein 2 (IGF2BP2) is involved in insulin resistance in HepG2 cells after arsenic exposure through the peroxisome-proliferator-activated receptor γ (PPAR-γ) / glucose transporter 4 (GLUT4) pathway. MethodsCell viability was determined using cell counting kit 8 (CCK8) and an appropriate NaAsO2 infection dose was determined. A cellular arsenic exposure model of HepG2 cells was established by four concentrations of NaAsO2 solution for 24 h (the experiment was divided into four groups: 0, 2, 4, and 8 μmol·L−1); HepG2 cells were firstly treated with pcDNA3.1-IGF2BP2 and pcDNA3.1-NC respectively for 6 h, then with 8 μmol·L−1 NaAsO2 for 24 h to establish a IGF2BP2 overexpression cell model (the experiment was divided into 4 groups: control, NaAsO2, NaAsO2+pcDNA3.1-IGF2BP2, and NaAsO2+pcDNA3.1-NC); finally the cells were subject to 100 nmol·L−1 insulin stimulation for 30 min. Glycogen and glucose in HepG2 cells were determined by glycogen and glucose assay kits; mRNA expression levels of IGF2BP2 were measured by quantitative real-time PCR; protein expression levels of IGF2BP2, PPAR-γ, and GLUT4 in HepG2 were detected by Western blot (WB); and the binding of IGF2BP2 to PPAR-γ and PPAR-γ to GLUT4 was verified by co-immunoprecipitation (CO-IP) experiment. ResultsThe results of CCK8 experiment showed a dose-effect relationship between NaAsO2 concentration and cell viability. When the concentration of NaAsO2 was ≥4 μmol·L−1 , the cell viabilities were lower than that of the control group (P <0.05). With the increasing dose of NaAsO2 infection, reduced glucose consumption and glycogen levels in HepG2 cells were found in the 2, 4, and 8 μmol·L−1 NaAsO2 treatment groups compared to the control group (P <0.05). The difference between the mRNA expression level of IGF2BP2 in the HepG2 cells treated with 4 or 8 μmol L−1 NaAsO2 and the control group was significant (P <0.05). In the IGF2BP2 overexpression cell model, compared with the control group, glucose consumption and glycogen levels were lowered in the NaAsO2 group (P <0.05), the mRNA expression level of IGF2BP2 and the protein expression levels of IGF2BP2, PPAR-γ, and GLUT4 in the cell membrane were all decreased (P <0.05). Compared with the NaAsO2 group, the glucose consumption and glycogen levels were increased in the NaAsO2+pcDNA3.1-IGF2BP2 group (P <0.05), and the mRNA expression level of IGF2BP2 and the protein expression levels of IGF2BP2, PPAR-γ, and GLUT4 in the cell membrane were all increased (P <0.05). The results of CO-IP experiments showed that IGF2BP2 interacted with PPAR-γ as well as PPAR-γ with GLUT4 protein. ConclusionIGF2BP2 is involved in arsenic exposure-induced insulin resistance in HepG2 cells by acting on the PPAR-γ/GLUT4 pathway.